A peripheral vision?. (2nd October 2021) - Biggs, Iain
ABSTRACT: This article reflects on the founding of the Journal of Visual Art Practice in 2001, as written from the perspective of the journal's inaugural editor. The article provides a brief overview of the history and context to the development of the journal, which includes the role of the National Association for Fine Art Education, a prior, associated publication, Drawing Fire, and also, critically, the outcomes of the Jarratt Report (1985) in the UK, which led to the framing of art practice as 'research', and inclusion in national research audits. The article considers some of inner tensions at stake in establishing the journal and outlines the hopes for the journal as considered in its early years. It concludes with questions regarding the future of the journal as something, in the words of Bruno Latour, which might 'cherish a maximum of alternative ways of belonging to the world'.